Implementation of lean manufacturing for process improvement in a company [electronic resource] - Abd. Razak Ab. Manap, 1985-; Fakulti Kejuruteraan Mekanikal (2009)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2009